The effect of acute fatigue on neuromuscular activation pattern during side-cutting in female team handball players - Zebis, M. K.; Bencke, J.; Kjaer, M.; Aagaard, P. (ISB Congress, 2005)
The purpose of this study therefore was to investigate if muscle fatigue induced by a simulated handball match would result in altered leg muscle motor patterns during side-cutting movements in female elite team handball players.